2021
DOI: 10.1002/jsfa.11071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alcoholic and acetous fermentations on the phenolic acids of Kei‐apple (Dovyalis caffra L.) fruit

Abstract: BACKGROUND The Kei apple is a tree found on the African continent. Limited information exists on the effect of alcoholic and acetous fermentation on the phytochemicals of Kei apple. The fruit has increased concentrations of l‐malic, ascorbic, and phenolic acids among other compounds. Juice was co‐inoculated with Schizosaccharomyces pombe (Sp) and Saccharomyces cerevisiae (Sc) to induce alcoholic fermentation (AF). Acetous fermentation followed AF, using an acetic acid bacteria (AAB) consortium. RESULTS Sacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Research shows that yeasts act in two ways during the fermentation process: They can capture polyphenols and release antioxidant compounds other than polyphenols from inside the cells and from the cell wall [ 39 ], i.e., by the release of bound and conjugated phenolic acids to their free form after cell wall degradation [ 71 ]. It was observed that the strain of yeast involved in alcoholic fermentation affected the profile of organic acids [ 72 ] as well as TCP and antioxidant potential [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that yeasts act in two ways during the fermentation process: They can capture polyphenols and release antioxidant compounds other than polyphenols from inside the cells and from the cell wall [ 39 ], i.e., by the release of bound and conjugated phenolic acids to their free form after cell wall degradation [ 71 ]. It was observed that the strain of yeast involved in alcoholic fermentation affected the profile of organic acids [ 72 ] as well as TCP and antioxidant potential [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the keywords found in the scientific articles are presented in the form of a word cloud (Figure 1b). It was noted that the most mentioned keyword was "phenolic" (n = 31), which shows that the characterization of the phenolic profile of vinegars was evident in the documents retrieved (Fernandes et al, 2019;Kim et al, 2020;Minnaar et al, 2021;Zou et al, 2017), followed by the words "vinegar" (n = 23), "antioxidant activity" (n = 14) and "fermentation" (n = 14). Moreover, it was possible to classify the scientific articles retrieved into subject areas (Table 1), where most studies were attributed to the areas of Agricultural and Biological Sciences (n = 57), and Biochemistry, Genetics and Molecular Biology (n = 34).…”
Section: Annual Evolution Subject Areas and Authors' Affiliationmentioning
confidence: 98%
“…The study revealed that sea buckthorn vinegar is a source of organic acids, in particular acetic acid (39.65 g/L), and of polyphenols such as gallic acid (763.89 mg/L) (Özdemir et al, 2022a). On the other hand, in the vinegar made with fruits of Dovyalis caffra L., the predominant polyphenol was chlorogenic acid, which showed mean values between 1,910.98 and 1,958.75 mg/L (Minnaar et al, 2021). In addition, Özdemir et al (2022a) reported that the major polyphenol found in vinegar made from fruits of Rosa canina L. was catechin (5.66 mg/L).…”
Section: Recent Research Studies On the Characterization Of Fruit Vin...mentioning
confidence: 99%
See 1 more Smart Citation